Biofilm inflection via chemically synthesized silver and nickel nanoparticles - Giriraj Tailor; Jyoti Chaudhary; Deepshikha Verma; Saurabh Singh; Ankita Mathur (Discover Applied Sciences)
Abstract Using a chemical process, urea and formaldehyde were converted into silver and nickel nanoparticles, which were then calcined at 800 °C. X-ray diffraction was used to verify the crystalline structure and chemical makeup of silver and nickel nanoparticles. Surface morphology and particle size distribution were studied using surface imaging techniques such as atomic force microscopy. Transmission electron microscopy and scanning electron microscopy were used to validate the spherical and porous-like morphology of the silver and nickel nanoparticles. The spherical shapes of silver and nickel metal ions are the reason for the apparent white dots. The X-ray diffraction analysis reveals that the particle sizes of nickel and silver metal ions are 13.71 nm and 41.43 nm, respectively. The synthetic Ag and Ni NPs were also tested for their ability to inhibit the growth of human pathogens, namely provisional Escherichia coli (E. coli) (Gram − ve) and Candida albicans (C. albicans) (Gram + ve), by screening for anti-biofilm activity. The study's findings indicate that synthetic Ag and Ni NPs have potential use in biological applications, such as anti-biofilm agents.